Juridical Analysis of the Sale and Purchase of Uncertified Plots in the Conception of Legal Certainty - Wahyu Hanggono; Fajar Taufan Riyanto; R. Sugiharto (Sultan Agung Notary Law Review, 2022)
This study aims to examine the juridical analysis of the sale and purchase of uncertified plots of land in Palangkaraya City in the conception of legal certainty, as well as to examine the legal responsibility for the parties to the sale and purchase of uncertified plots of land in Palangkaraya City. This research method uses an empirical juridical approach. The research specifications used are library research and field research. The data sources used are primary data obtained from interviews. Based on the results of the study, it can be concluded: 1) that the sale and purchase of uncertified plots in Palangkaraya City still causes many legal problems, especially regarding land ownership disputes, because the proof of ownership of the plot of land in the form of a Land Declaration Letter (SPT) and proof of sale and purchase in the form of a Land Transfer Statement (SPPT) still does not have legal force. This proves that Gustav Radbruch's theory is still not working well; 2) The legal liability carried out by the seller of the land plot is in principle in accordance with the theory of legal responsibility put forward by Hans Kelsen which states that a person is legally responsible for a certain act or that he bears legal responsibility when committing an act that is contrary to the law.